2022
DOI: 10.29244/jfs.v7i2.38993
|View full text |Cite
|
Sign up to set email alerts
|

The Process and Output of Family Resilience on Lebak Flash Flood Victims in 2020 Who Stay in Temporary Housing

Abstract: The flash flood disaster that hit Lebak Regency in 2020 caused the family to be in a state of crisis. Families need a process to survive and come back empowered. This study aims to analyze the process and output of the resilience of the victims' families using the RESILIENSI-GA instrument. The research design was a cross-sectional study and a retrospective study. The sample was selected by purposive sampling, precisely 60 victims’ families who stay in temporary housing at Lebak Regency. Collected data in March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The areas affected by flash floods and DPs will be emptied by residents, so that affected families cannot build houses in these areas. Thus, affected families living in DPs will be relocated from shelters, independently, and jointly with other local families within a predetermined time [15]. This is not the case with the DBM intended for the affected families in Desa Bungur Mekar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The areas affected by flash floods and DPs will be emptied by residents, so that affected families cannot build houses in these areas. Thus, affected families living in DPs will be relocated from shelters, independently, and jointly with other local families within a predetermined time [15]. This is not the case with the DBM intended for the affected families in Desa Bungur Mekar.…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from the BPBD Lebak Regency (2020), flash floods resulted in nine deaths, two missing people, 26 damaged bridges, 680 severely damaged houses, 262 moderately damaged houses, 646 lightly damaged houses, and 4,618 displaced families [2]. A study on the resilience of families affected by the Lebak Banten flash flood found that for three and a half months after the disaster, families were in crisis due to loss of assets, experienced deep trauma and relied only on humanitarian assistance to meet their needs were instructed not to occupy the area in which they lived, which was affected by the flash flood [15]. Families who experienced total damage to their homes were required to live in evacuation posts designed as temporary shelters for the affected families.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience is a dynamic process that leads to positive adaptation in the face of difficult situations (Sunarti, 2013). Resilience is the capacity of individuals to overcome and adapt to difficulties to grow strength and be free from pressure.…”
Section: Discussionmentioning
confidence: 99%
“…During adolescence, physical, behavioral, and attitudinal changes take place rapidly (Hurlock, 2002). The togetherness of adolescents and families is essential, especially in developing human resources (Sunarti, 2013). However, adolescents today are increasingly vulnerable in facing the dynamics of life due to socioeconomic changes, the development of information and technology, and globalization so adolescents are required to have resilience so as not to interfere with developmental tasks, quality of life, and their future (Sunarti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Toughness is defined by KBBI (2021) as strength, tenacity, and steadfastness. Family resilience is family strength that arises from strong feelings as a family in controlling life's events and difficulties, viewing life as meaningful, prioritizing involvement in family activities, and having a commitment to learn to explore things and challenges, as well as new experiences (Sunarti, 2013). A resilient family can respond positively to crisis conditions, in a way that is unique according to the context and perspective of the family towards the problems faced (Hawley, 1966).…”
Section: Introductionmentioning
confidence: 99%